O PROCESSO DE EDUCAÇÃO CONTINUADA: ESTUDO DE CASO NO EIXO DE CAPACITAÇÃO DE SMS DENTRO DA UNIVERSIDADE CORPORATIVA PETROBRAS - Queiroz Junior, Durval Vilar de (2007)
The development of people in organization have to be continue and permanent character, linked with the objective of the business. In this aspect, the organizations are investing more and more in structural education by creating a training and development department or by the creation of a partnership with educational institutions. These kind of concerns come intending to fill up blank spaces occurred at the formal education, search for information in different places and assure the permanent learning, trough a continuous education. In the order hand, the importance at one process of Health, Safety and Environment HSE that look to search the excellence in this area, contributing for reduce the accident, bring the necessity to used rather that possibility a real change in the organizational culture. By this way, based in a research with an explorer nature, developed inside one energy enterprise it has been made a study of several cases, inquiring the evaluation of the corporative university actuation, focus straight to the capacitacion of the health, safety and environment HSE activities. As a result, we can realize the importance of PETROBRAS Corporative University in this process, a measure that coming possibility the dissemination, all over the company, a new culture, looking forward aspects to reduce accident, minimizing effects to environment and improve the quality healthy to the employee, helping to take the company as so long for excellence in HSE